CORRELATION BETWEEN READING INTEREST AND ENGLISH ACADEMIC ACHIEVEMENT OF SIXTH SEMESTER EFL INDONESIAN STUDENTS - Zefri Asrianza; Azhar Aziz Lubis; Muhammad Fadhli (UNIB Press, 2026)
This study aims to investigate how is reading interest and English academic achievement as well as the correlation between reading interest and English academic achievement of English Department study program students at the University of Bengkulu. The population of this study was students of the English Department Study Program at the University of Bengkulu with a sample of 35 students. This research is correlational research with quantitative methods, and uses questionnaires and documentation as instruments. The results of this study are, the reading interest of students in semester 6 of English education was quite high, as could be seen from a total of 88% of the 35 samples who had a reading interest score which is categorized as high. For English Academic Achievement, the majority of students have scores that are also high, namely 97% of the 35 samples are categorized as having very high scores. For the correlation between reading interest and English academic achievement, a strong correlation was obtained with a score of 0.556607. It also shows if Ho is rejected and Ha is accepted. Moreover, several suggestions for teachers, students and future researchers are addressed in the present study.